Peran Guide Arsip Fisik dalam Meningkatkan Efektivitas Temu Kembali Arsip Warkah PTSL di Kantor Pertanahan Kabupaten Ponorogo - Adz Zakia Fitriana Hafsah; Mahmudatul Himmah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This article discusses the role of physical archive guides in improving the effectiveness of retrieving Complete Systematic Land Registration (PTSL) land record archives at the Ponorogo Regency Land Office. The increasing volume of PTSL land records requires an effective retrieval system to support fast and accurate public services. However, the retrieval of physical archives often faces obstacles, particularly in identifying archive locations within storage boxes. This study uses a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. Data were analyzed by comparing archive retrieval conditions before and after the implementation of physical archive guides. The results show that the use of physical archive guides plays an important role in improving archive retrieval effectiveness, as indicated by faster retrieval time, easier archive identification, and more orderly archive arrangement. The implementation of physical archive guides serves as a simple yet effective strategy to support the retrieval of PTSL land record archives and can be used as a basis for further development of archive retrieval systems